Serum Amyloid A 4 as a Common Marker of Persistent Inflammation in Patients with Neovascular Age-Related Macular Degeneration and Polypoidal Choroidal Vasculopathy - Liu Q; Sun S; Yang Z; Shao Y; Li X (Journal of Inflammation Research, 2023)
Qingyan Liu,1,2,* Shuo Sun,1,* Zhengwei Yang,1,* Yan Shao,1 Xiaorong Li1 1Tianjin Key Laboratory of Retinal Functions and Diseases, Tianjin Branch of National Clinical Research Center for Ocular Disease, Eye Institute and School of Optometry, Tianjin Medical University Eye Hospital, Tianjin, 300384, People’s Republic of China; 2Department of Ophthalmology, Anhui NO.2 Provincial People’s hospital, Hefei, 230041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Shao; Xiaorong Li, Email 13820179302@163.com; xiaorli@163.comBackground: Neovascular age-related macular degeneration (nAMD) and its subtype, polypoidal choroidal vasculopathy (PCV), are common choroidal vasculopathies. Although they share many common clinical manifestations and treatment strategies, a lack of comprehensive analysis of these conditions means that it is difficult for researchers to further explore the common pathomechanisms of nAMD and PCV. The aim of this study was to characterize aqueous humor (AH) proteome alterations and identify a novel biomarker related to both nAMD and PCV.Methods: Liquid Chromatography with tandem mass spectrometry (LC-MS/MS) was adopted to analyze the AH proteomes of nAMD, PCV and controls. The target protein was validated using the enzyme-linked immunosorbent assay (ELISA) and subjected to receiver operating characteristic (ROC) curve analysis.Results: A total of 737 different proteins were identified in all the groups, of which 544 were quantifiable. The bioinformatics analysis suggested that immune response activation is the essential event in both nAMD and PCV. Serum amyloid A (SAA) 4 is closely associated with a number of chronic inflammatory diseases, and it was enriched as the hub protein. ROC analysis showed that SAA4 could distinguish both nAMD and PCV from the controls.Conclusion: This comprehensive study provides insights into, and furthers our understanding of, the pathological mechanism of nAMD and PCV. Additionally, the SAA4 level alteration may serve as a common biomarker of nAMD and PCV.Keywords: serum amyloid A 4, inflammation, neovascular age-related macular degeneration, polypoidal choroidal vasculopathy